Sistem Informasi Peminjaman dan Pengembalian Rekam Medis Rawat Inap Berbasis Web di RSUD Haji Surabaya - Ervina Rachmawati; Sitti Fa’Isil Karomah; Selvia Juwita Swari; Donny Adhasari Hasan (Jurnal Teknologi Informasi dan Multimedia, 2022)
The recording, borrowing and returning of medical record documents at the Haji Hospital in Surabaya still uses a manual borrowing expedition book in the filing section. The medical record documents returned are not in accordance with the SOP (Standard Operating Procedure) and SPM (Minimum Service Standard) of the hospital. The purpose of this study was to design and create a web-based information system for borrowing and returning medical records at the Haji Hospital in Surabaya. The method used in this research is waterfall. The stages of the waterfall method are requirements analysis, system design, system creation and system testing. Data collection was done by interview, observation, and documentation. The result of this research is a web-based information system for borrowing and returning medical records. Suggestions for the Haji Hospital of Surabaya are expected to be able to use a web-based information system for borrowing and returning medical records to facilitate the electronic recording process, speed up reporting and reduce the incidence of delays.